Differentiated Thyroid Carcinoma in Pediatric Age: Genetic and Clinical Scenario - Galuppini, Francesca; Vianello, Federica; Censi, Simona; Barollo, Susi; Bertazza, Loris; Carducci, Sofia; Colato, Chiara; Manso, Jacopo; Rugge, Massimo; Iacobone, Maurizio; Watutantrige Fernando, Sara; Pennelli, Gianmaria; et al. (Frontiers in Endocrinology, 2019)
Introduction. Follicular-derived differentiated thyroid carcinoma (DTC) is the most common endocrine and epithelial malignancy in children. The differences in the clinical and pathological features of pediatric versus adult DTC could relate to a different genetic profile. Few studies are currently available in this issue, however, and most of them involved a limited number of patients and focused mainly on radiation-exposed populations. Materials and methods. We considered 59 pediatric patients who underwent surgery for DTC between 2000 and 2017. RET/PTC rearrangement was investigated with fluorescent in situ hybridization and real-time polymerase chain reaction. Sequencing was used to analyze mutations in the BRAF, NRAS, PTEN, PIK3CA genes, and the TERT promoter. The pediatric patients’ clinical and molecular features were compared with those of 178 adult patients. Results. In our pediatric sample, male gender and age <15 years coincided with more extensive disease and more frequent lymph node and distant metastases. Compared with adults, the pediatric patients were more likely to have lymph node and distant metastasis, and to need second treatments (p<0.01). In all, 44% of the pediatric patients were found to carry molecular alterations. RET/PTC rearrangement was confirmed as the most frequent genetic alteration in childhood DTC (24.6%) and correlated with aggressive features. BRAFV600E was only identified in 16% of the pediatric DTCs, while NRASQ61R, NRASQ61K and TERTC250T mutations were very rare. Conclusions. Pediatric DTC is more aggressive at diagnosis and more likely to recur than its adult counterpart. Unlike the adult disease, point mutations have no key genetic role.